The Long-Term Impact of Systemic Student Support in Elementary School: Reducing High School Dropout - Terrence J. Lee-St. John; Mary E. Walsh; Anastasia E. Raczek; Caroline E. Vuilleumier; Claire Foley; Amy Heberle; Erin Sibley; Eric Dearing (SAGE Publishing, 2018)
Dropping out of high school has adverse consequences, including negative effects on employment, lifetime earnings, and physical health. Students often fail to complete high school for complex reasons that often manifest long before they reach high school. This study examines the link between participation in a comprehensive elementary school student support intervention and high school dropout. In this study, students who attended intervention elementary schools in a large, urban, high-poverty district during 2001-2014 ( N =894) were compared to students who did not attend intervention schools ( N =10,200). Likelihood of dropping out in grades 9-12 was estimated using propensity score-weighted Discrete Event History Analysis. Intervention students had approximately half the odds of dropout ( p <.001); the probability of dropout for intervention was 9.2%, compared to 16.6% for non-intervention students. Individually tailored student support interventions during elementary school can lead to lasting and meaningful effects.